1982
DOI: 10.1017/s0021859600031245
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying seed rate on the yield and yield components of oil-seed rape (Brassica napus)

Abstract: Two varieties of oil-seed rape were drilled in 1979-81 at a range of seed rates. Percentage establishment, plant weight, height, and the ratio of seed to total aboveground dry matter were lower in high-density plots. Seed yields were not increased when the seed rate was raised from 9-0 to 13-5 kg/ha (Expts 1 and 2) or from 4-5 to 18-0 kg/ha (Expt 3) owing to a compensating reduction in the number of pods per plant. Seed quality and 1000-seed weight were not influenced by the seed-rate treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 4 publications
5
13
0
Order By: Relevance
“…Morrison et al (1990 Scarisbrick et al (1982) who reported that the lowest harvest index occurred at the highest seeding rate, while no differences occurred at lower seeding rates (for seeding rates between 4.5 and 13.5 kg ha-r;. Similar results were obtained by Degenhardt and Kondra (1981a) (Loof 1960 (1915,1977) …”
supporting
confidence: 74%
“…Morrison et al (1990 Scarisbrick et al (1982) who reported that the lowest harvest index occurred at the highest seeding rate, while no differences occurred at lower seeding rates (for seeding rates between 4.5 and 13.5 kg ha-r;. Similar results were obtained by Degenhardt and Kondra (1981a) (Loof 1960 (1915,1977) …”
supporting
confidence: 74%
“…In general, Brassica napus cultivars lodge after pod filling, particularly in situations with high plant populations and therefore weaker stems (Scarisbrick et al. 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the final seed yield is contributed by the terminal raceme on the main stem and pods on the primary branches in rape seed genotypes. Pods on secondary branches are of minor importance in the determination of seed yield in this crop (Campbel and Kondra 1978, Geisler 1980, Scarisbrick et al. 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Plants with more space and less competition for light and nutrients grow to a larger size, as shown with maize (Edmeades and Daynard, 1979) and oilseed rape (Morrison et al, 1990). Compensatory growth at lower seeding rates has been shown to result in similar yields per hectare for both oilseed rape (Scarisbrick et al, 1982) and maize (Marsalis et al, 2010). Moreover, planting fewer treated seeds per unit areas would have the added advantage of causing less total environmental contamination, given that only a small proportion (2-20%) of the chemical applied to seeds is absorbed by the plant (Shmuck et al, 2001;Sur andStork, 2003 Sur andStork, 2003).…”
Section: Discussionmentioning
confidence: 97%